Utilization of Picture Story Books of Sister and Kitten by Wulanita Kuswotanti As A Stimulation of Early Childhood Empathy Skills - Ma’rifah Mualim, Siti (Lembaga Kajian Nusantara Raya UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2024)
Storybooks are one of the media and also a learning tool that can improve various abilities of early childhood, such as developing children's thinking and imagination, developing children's speaking skills, developing children's socialization power and means of communication between children and their environment. The ability of empathy can be grown and developed in children through various approaches including exemplary, stories or stories, stories related to empathy, namely stories that can foster children's empathetic attitudes towards the characters or events that occur in the story. As in the contents of the picture story book Adik and Kitten by Wulanita Kuswotanti can provide stimulation of early childhood empathy skills, so that children have good empathy skills. This research uses descriptive qualitative research methods with the type of literature study (literature) with data collection techniques using storybook documentation and other journals as secondary data sources and descriptive content analysis by reading, noting important things, and analyzing various quotes and fragments of paragraphs that are considered to contain empathy values.